FEASIBILITY ANALYSIS OF GOURAMI GROWING BUSINESS (Case Study: Kota Galuh Village, Serdang Bedagai Regency) - Athalla Ariq Trianda (Agripreneur : Jurnal Pertanian Agribisnis, 2020)
The purpose of this study was to identify the availability of inputs (land, capital, labor, seeds, feed) for the gouramy business and to find out whether the gouramy rearing business was feasible or not feasible to develop in the research area. The method of determining the research area used is purposive. The analytical method used is Break Event Point (BEP) and R/C Ratio. The results showed: Production inputs such as (Land, Capital, Seeds, Labor, Seedlings, Feed) were available and Based on the feasibility analysis, the gouramy rearing business was declared feasible because production volume > Production BEP, Price > BEP Price, and R/C > 1.